Physical Condition of Athletes of the All Indonesian Athletics Association, Pesawaran Regency - Andri Prasetiyo; Reza Adhi Nugroho; Arif Alexander Bastian (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is based on the absence of an athlete database on the physical condition of PASI athletic athletes in the Pesawaran Regency. This study intends to determine how good the physical condition of PASI athletes is in Pesawaran Regency. The test results of each component of different physical conditions are converted into T scores and added up. The components of the physical condition studied included the speed of leg muscle strength, arm and shoulder muscle strength, flexibility, and endurance. This type of research is a quantitative descriptive study with a survey method and test and measurement data collection techniques. The population in this study consisted of 18 athletes, consisting of 10 male athletes and eight female athletes. This study uses a saturated sampling technique. The results of the research on the physical condition of PASI athletes in Pesawaran Regency show the results for the "good" category, and there are ten athletes with a percentage of 55.55%; in the "enough" category, there are four athletes with a percentage of 22.5%; in the "less" category, there are three athletes with a percentage of 16.5%; and in the "very poor" category, there is one athlete with a percentage of 5.5%. The physical condition of PASI athletes in Pesawaran Regency is dominant, or good". Athletes still in the category of less or less need more maximum training so that their physical condition can be even better.